2011
DOI: 10.1017/s0007114511000420
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selenium-enriched milk proteins and selenium yeast on plasma selenium levels and rectal selenoprotein gene expression in human subjects

Abstract: Certain forms of dietary Se may have advantages for improving human Se status and regulating the risk for disease, such as cancers, including colorectal cancer (CRC). The present study compared the effects of a Se-enriched milk protein (dairy-Se) with a Se-rich yeast (yeast-Se) on plasma Se levels and rectal selenoprotein gene expression since we reasoned that if these genes were not regulated, there was little potential for regulating the risk for CRC in this organ. A total of twenty-three healthy volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…Furthermore, they found no relationship between selenoprotein P and QUICKI (quantitative insulin sensitivity index), a marker of insulin resistance [5]. Evidence from two small interventions also fails to support a diabetogenic effect of Se; one study found no significant disturbances in plasma glucose after six weeks of supplementation with 150 µg/d Se as dairy- or yeast-Se [46] while the other, a randomized, controlled trial, found that 200 µg Se/d as yeast-Se for six weeks significantly lowered fasting serum insulin and HOMA-IR (homeostasis model assessment of insulin resistance) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found no relationship between selenoprotein P and QUICKI (quantitative insulin sensitivity index), a marker of insulin resistance [5]. Evidence from two small interventions also fails to support a diabetogenic effect of Se; one study found no significant disturbances in plasma glucose after six weeks of supplementation with 150 µg/d Se as dairy- or yeast-Se [46] while the other, a randomized, controlled trial, found that 200 µg Se/d as yeast-Se for six weeks significantly lowered fasting serum insulin and HOMA-IR (homeostasis model assessment of insulin resistance) [47].…”
Section: Discussionmentioning
confidence: 99%
“…While increases in plasma Se levels were similar in both Se-supplemented groups, dairy-Se was more effective to stimulate gene expression of selenoproteins. Dairy-Se increased rectal SeP, GPx1, and GPx2 mRNA levels, whereas Se-yeast only increased rectal SeP mRNA levels (33). First attempts have been undertaken to identify suitable biomarkers of Se status in selected tissues.…”
Section: Optimization Of Selenoprotein Biosynthesis Through Se Supplementioning
confidence: 99%
“…Eighteen (24%) studies reported the number of EBs used for molecular testing; the median (range) mean number of EBs per patient was 2.1 (1 to 6.6 biopsies) . Only one study reported the location within the tumour from which the biopsy was obtained …”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported a minimum tumour cell density required in the resection specimen for comparison using cut‐offs of 10% or 50% tumour cells . No association was seen among studies between the mean number of biopsies obtained per patient and the concordance of biomarker testing between biopsy and resection specimen . Results for the different investigative methodologies are detailed below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation